2008
DOI: 10.1016/j.jcomdis.2008.03.003
|View full text |Cite
|
Sign up to set email alerts
|

The human lexinome: Genes of language and reading

Abstract: Within the human genome, genetic mapping studies have identified 10 regions of different chromosomes, known as DYX loci, in genetic linkage with dyslexia, and two, known as SLI loci, in genetic linkage with Specific Language Impairment (SLI). Further genetic studies have identified four dyslexia genes within the DYX loci: DYX1C1 on 15q, KIAA0319 and DCDC2 on 6p22, and ROBO1 on 13q. FOXP2 on 7q has been implicated in the development of Speech-Language Disorder.No genes for Specific Language Impairment have yet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 41 publications
0
15
0
4
Order By: Relevance
“…An intense literature [Cody et al, 2007;Smith, 2007;Gibson and Gruen, 2008;Fisher and Scharff, 2009;Caglayan, 2010;Newbury and Monaco, 2010;Scherer and Dawson, 2011] and database (http://www.mindspec.org/autdb.html) research revealed 244 genes associated with human-specific communication ( table 1 ). These genes have been associated with autism spectrum, reading, speech, and language disorders.…”
Section: Database Analysesmentioning
confidence: 99%
“…An intense literature [Cody et al, 2007;Smith, 2007;Gibson and Gruen, 2008;Fisher and Scharff, 2009;Caglayan, 2010;Newbury and Monaco, 2010;Scherer and Dawson, 2011] and database (http://www.mindspec.org/autdb.html) research revealed 244 genes associated with human-specific communication ( table 1 ). These genes have been associated with autism spectrum, reading, speech, and language disorders.…”
Section: Database Analysesmentioning
confidence: 99%
“…The current status of RD genetic association efforts, reviewed more thoroughly elsewhere (Gibson CJ and JR Gruen, 2008; Paracchini S et al, 2007), underscores the complexity of RD genetics. The composite evidence clearly shows a strong genetic risk; however, even the most consistently associated genetic loci and genes have not been significantly associated with RD in all sample populations.…”
Section: Genetics Of Rdmentioning
confidence: 99%
“…Difficulties in learning to read may have a biological cause, the neural connections may not organize themselves accordingly during the neurological development since the fetal stage till the first childhood due to both genetic [52,1,35,42,17,51,38,43,15,19] and environmental factors, such as malnutrition [39,21,41], preterm birth [31], mother depression [21], stress suffered by the mother during pregnancy [24,41], use of drugs [41,51,8], among others.…”
Section: Introductionmentioning
confidence: 99%